2D MXene Additive‐Induced Treatment Enabling High‐Efficiency Indoor Organic Photovoltaics. Issue 1 (31st October 2022) - Saeed, Muhammad Ahsan; Kim, Tae Hyuk; Ahn, Hyungju; Park, Na Won; Park, JaeHong; Choi, Hyosung; Shahzad, Asif; Shim, Jae Won
Abstract: The surge of Internet‐of‐everything applications over the past decade demands the adoption of novel material design and device engineering strategies for the development of state‐of‐the‐art organic photovoltaics (OPVs) in low‐light indoor environments. Owing to their excellent optoelectronic properties, two‐dimensional MXenes possess outstanding potential in this regard. Herein, an unprecedented indoor power conversion efficiency (PCE) of 33.8% under light‐emitting‐diode (LED) illumination (1000‐lx) is secured by additive‐induced treatment of MXene in polymer‐donor:non‐fullerene‐acceptor‐based organic photoactive layer. The remarkable indoor performance of MXene OPVs mainly originates from the enhanced absorption, compact molecular packing, and smooth surface morphology with a reduced number of grain boundaries in the photoactive layer, resulting in an improved fill factor and balanced charge transport and extraction characteristics with suppressed recombination, thereby producing an impressive indoor PCE. In addition, the presence of MXene in the photoactive layer facilitates polaron‐pair dissociation owing to improved free‐charge generation, leading to enhanced photoconductivity. This performance represents the highest PCE among the OPVs measured under indoor illumination. This work highlights the promising prospect of 2D MXene and its composites for indoor light energy harvesting applications. Abstract : The PM6:Y6:MXene‐based organic photovoltaics demonstrates unprecedented high power conversion efficiency of 33.8% under light‐emitting‐diode illumination (1000‐lx). 2D emerging MXene flakes in the organic photoactive layer provide high photoconductivity, smooth surface morphology with low grain boundaries, enhanced absorption, and ordered molecular packings along with tighter π‐π stacking resulting in reduced charge recombination with effective charge transport and collection properties.